2000
DOI: 10.1111/j.1469-7793.2000.t01-2-00291.x
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine phosphorylation modulates the osmosensitivity of volume‐dependent taurine efflux from glial cells in the rat supraoptic nucleus

Abstract: In the supraoptic nucleus, taurine, selectively released in an osmodependent manner by glial cells through volume‐sensitive anion channels, is likely to inhibit neuronal activity as part of the osmoregulation of vasopressin release. We investigated the involvement of various kinases in the activation of taurine efflux by measuring [3H]taurine release from rat acutely isolated supraoptic nuclei. The protein tyrosine kinase inhibitors genistein and tyrphostin B44 specifically reduced, but did not suppress, both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
36
2

Year Published

2000
2000
2008
2008

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 50 publications
(100 reference statements)
3
36
2
Order By: Relevance
“…In Intestine 407 cells, however, in clear contrast to the activation of VRAC (53,55), the release of taurine was found to be independent of tyrosine kinases and PtdIns 3-kinase and did not involve p21 rho . A similar low sensitivity to genistein has been reported for isolated rat supraoptic astrocytes (6). Taken together, these results indicate not only that the release of taurine does not involve VRAC in intestine 407 cells but also that distinct signaling pathways are involved in the regulation of Cl Ϫ and taurine efflux (54).…”
Section: Discussionsupporting
confidence: 57%
“…In Intestine 407 cells, however, in clear contrast to the activation of VRAC (53,55), the release of taurine was found to be independent of tyrosine kinases and PtdIns 3-kinase and did not involve p21 rho . A similar low sensitivity to genistein has been reported for isolated rat supraoptic astrocytes (6). Taken together, these results indicate not only that the release of taurine does not involve VRAC in intestine 407 cells but also that distinct signaling pathways are involved in the regulation of Cl Ϫ and taurine efflux (54).…”
Section: Discussionsupporting
confidence: 57%
“…In cell culture models, tyrosine kinase activity is up-regulated by hypotonic stress (9, 10) and is required for immediate-early gene transcription and expression (10,32). Pharmacological inhibition of tyrosine kinase activity blocks, and potentiation of tyrosine kinase activity inhibits, regulatory volume decreaseassociated efflux of cations (9), chloride (33)(34)(35)(36)(37)(38)(39), and the amino acid osmolyte, taurine (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…An alternative explanation for the effect of kinase inhibitors on isotonic volume in spermatozoa might have been that they caused enhancement of taurine flux (e.g. in glial cells; Deleuze et al 2000); however, it has recently been shown that taurine efflux is not essentially involved in volume control in boar or human spermatozoa, although it does play a role in mouse sperm RVD (Yeung et al 2003, Petrunkina et al 2004a. While staurosporine, lavendustin and Bis I led to comparable increases in isotonic volume, the effect of the PKC inhibitor Bis X was less.…”
Section: Discussionmentioning
confidence: 99%